2006
DOI: 10.1007/s00277-006-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-eclampsia on complete blood count, platelet count and mean platelet volume

Abstract: Pre-eclampsia is a condition observed during pregnancy and threatens the life of both mother and foetus. There are studies, which suggest platelets play a major role in the pathogenesis of pre-eclampsia. The aim of this study is to compare the complete blood count (CBC) parameters, especially platelet count and mean platelet volume (MPV), in pre-eclamptic and normal pregnant women and to evaluate whether these parameters have a prognostic significance in determining the severity of eclampsia. The study and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 13 publications
5
51
3
2
Order By: Relevance
“…Ceyhan et al reported comparable platelet counts and MPV among 56 preeclamptic, 8 severe pre-eclamptic, and 43 control subjects. However, in that study sample size was small and NLR was not investigated (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Ceyhan et al reported comparable platelet counts and MPV among 56 preeclamptic, 8 severe pre-eclamptic, and 43 control subjects. However, in that study sample size was small and NLR was not investigated (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Increased MPV occurs before onset of PE symptoms. Therefore, it may be a valuable marker for development of PE [13]- [15]. Furthermore, it has been suggested that PDW can be a practical tool to evaluate activation of coagulation or thrombocytosis-related disease [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some conflicting finding has been published regarding the changes in the platelet indices in well pregnant women. Some researchers found no change in the values of these indices between patients and controls (Ceyhan, 2006, Freitas, 2013. Whereas others demonstrated difference in platelet index values (Yong, 2014;Dundar, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas others demonstrated difference in platelet index values (Yong, 2014;Dundar, 2008). This consistency of those studies may be due to the varying methods of platelet indices determination (Ceyhan, 2006). P-LCR was significantly increased in patients with thrombocytopenia and decreased in thrombocytosis condition.…”
Section: Discussionmentioning
confidence: 99%